Efficient and selective cleavage of the tert-butoxycarbonyl (Boc) group under basic condition - Mohapatra, Debendra K.; Durugkar, Kulbhushan A. (Arkivoc, 2005)
A simple, efficient and mild method for the selective cleavage of tert-butoxycarbonyl (Boc) from dicarbamates and a carbonyl or aromatic ring in conjugation with the nitrogen atom bearing the Boc-group is described under basic condition.
Keywords: alpha-amino acids; celogenitins; di-t-butylimidodicarbonate; racemization; Selective deprotection

Short synthesis of (2S,3S)-3-hydroxypipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Pawar, Kailash P. (Tetrahedron Letters, 2013)
A convenient synthesis of (2S,3S)-3-hydroxypipecolic acid starting from cheap and abundant L-(+)-tartaric acid has been achieved. The strategy employs selective ester reduction and reductive lactamization as key steps. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Reductive lactamization; Selective deprotection; Wittig reaction